2014
DOI: 10.1186/1471-2407-14-930
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in prostate cancer: functional importance and potential as circulating biomarkers

Abstract: BackgroundThis non-systematic review article aims to summarise the progress made in understanding the functional consequences of microRNA (miRNA) dysregulation in prostate cancer development, and the identification of potential miRNA targets as serum biomarkers for diagnosis or disease stratification.ResultsA number of miRNAs have been shown to influence key cellular processes involved in prostate tumourigenesis, including apoptosis-avoidance, cell proliferation and migration and the androgen signalling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 81 publications
4
56
0
4
Order By: Relevance
“…Similar to cell‐free nucleic acids (cfNAs), exosomes can potentially be utilized for various analyses such as gene expression profiling and genetic analysis. For example, previous studies have found differential miRNA levels in exosomes of hepatocytes compared to controls and an upregulation of miRNA levels in the exosomes of pancreatic cancer patients, but rarely in controls . While these studies suggest a successful use of exosome analysis in cancer diagnosis, future studies should validate these findings in other cancer types including breast cancer.…”
Section: Liquid Biopsy Componentsmentioning
confidence: 91%
“…Similar to cell‐free nucleic acids (cfNAs), exosomes can potentially be utilized for various analyses such as gene expression profiling and genetic analysis. For example, previous studies have found differential miRNA levels in exosomes of hepatocytes compared to controls and an upregulation of miRNA levels in the exosomes of pancreatic cancer patients, but rarely in controls . While these studies suggest a successful use of exosome analysis in cancer diagnosis, future studies should validate these findings in other cancer types including breast cancer.…”
Section: Liquid Biopsy Componentsmentioning
confidence: 91%
“…Another four selected miRNAs (miR-1246, miR-4644, miR-3976 and miR-4306) were found to be significantly upregulated in the serum exosomes of pancreatic cancer patients but rarely in control groups, and the concomitant evaluation of pancreatic cancer-initiating cells and miRNA serum exosome marker panels even reached a diagnostic specificity of 0.93 (95% CI, 0.81-0.98) [81]. The above studies offer considerable evidence that exosome miRNAs can be applied as a valuable tool in cancer diagnosis; however, the heterogeneous results (even among similar cancer types) hamper the interpretation and reliability of miRNAs as cancer biomarkers in clinical diagnosis [82, 83]. Furthermore, several biomarkers in serum exosomes have been suggested to be good candidate diagnostic and theranostic markers in patients with colorectal cancer, pancreatic cancer and breast cancer, such as HSP60 and GPC1, which are expected to be validated in more studies with larger samples.…”
Section: Diagnosis and Prognosis Assessmentmentioning
confidence: 99%
“…In cancer, they are deregulated and involved in tumorigenesis, tumor progression, metastasis and resistance to treatment. Furthermore, miRNAs have recently been proposed as promising biomarkers for cancer diagnosis and follow-up studies on disease progression, because they can be detected in body fluids, carried by MPs or associated with proteins that protect them from degradation (Fujiwara et al 2014;Inns and James 2015;Jackson et al 2014;Lindner et al 2015;Liu and Xiao 2014;Pimentel et al 2014). Several groups are attempting to uncover the underlying mechanisms involved in miRNA selection, release and transport to blood fluids and their role in cancer (Arroyo et al 2011;Li et al 2012;Turchinovich et al 2011).…”
Section: Microparticles and Micrornasmentioning
confidence: 98%